2021
DOI: 10.3390/educsci11110743
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Models to Implement Effective STEM Research Experience Programs in High School Students

Abstract: High school research experience programs (HSREPs) provide opportunities for true science education and expose students to scientific investigations in laboratory settings. Various HSREPs models have been practiced to shape students’ research understandings; however, a systematic comparison of the success, challenges, and opportunities of these HSREPs has not been gauged. This article compares the effectiveness of such science, technology, engineering, and mathematics (STEM) based HSREP models reported in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…The importance of active learning in enhancing students’ self-efficacy, self-concept, and conceptual understanding cannot be overstated. Building on the groundwork of Bandura’s motivational theory, numerous studies have robustly demonstrated the profound impact of inquiry-based learning and authentic hands-on experiments on boosting students’ self-efficacy, science identity, and retention across STEM fields and diverse demographic groups (e.g., Swan et al, 2018, Ahmad et al, 2021, Jeskova et al, 2022, Wilczek et al 2022, Sperling et al, 2024, Broder et al, 2019, Indorf et al, 2019). These studies lend robust support to our empirical observations, highlighting the critical importance of integrating real-world experimentation and inquiry-driven methods to significantly enhance students’ conceptual comprehension and sense of confidence in their ability to perform experiments and apply these concepts.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of active learning in enhancing students’ self-efficacy, self-concept, and conceptual understanding cannot be overstated. Building on the groundwork of Bandura’s motivational theory, numerous studies have robustly demonstrated the profound impact of inquiry-based learning and authentic hands-on experiments on boosting students’ self-efficacy, science identity, and retention across STEM fields and diverse demographic groups (e.g., Swan et al, 2018, Ahmad et al, 2021, Jeskova et al, 2022, Wilczek et al 2022, Sperling et al, 2024, Broder et al, 2019, Indorf et al, 2019). These studies lend robust support to our empirical observations, highlighting the critical importance of integrating real-world experimentation and inquiry-driven methods to significantly enhance students’ conceptual comprehension and sense of confidence in their ability to perform experiments and apply these concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies in both Qatar and worldwide have thus focused on the challenges that educational systems face in their efforts to raise the number of students who successfully enter and leave the STEM education system (Seymour, 2002;Singer et al, 2012;Ahmad et al, 2021;Sellami et al, 2022Sellami et al, , 2023. Much of the attention is drawn to the reasons that contribute to students dropping out of STEM careers, including but not limited to students' interests, the nature of educational environments, and the teaching-learning practices employed (National Academies of Sciences and Medicine, 2016).…”
Section: Introductionmentioning
confidence: 99%